Enhancing Photocatalytic Hydrogen Production via the Construction of Robust Multivariate Ti‐MOF/COF Composites. Issue 3 (9th December 2021) - Chen, Cheng‐Xia; Xiong, Yang‐Yang; Zhong, Xin; Lan, Pui Ching; Wei, Zhang‐Wen; Pan, Hongjun; Su, Pei‐Yang; Song, Yujie; Chen, Yi‐Fan; Nafady, Ayman; Sirajuddin,; Ma, Shengqian
Abstract: Titanium metal–organic frameworks (Ti‐MOFs), as an appealing type of artificial photocatalyst, have shown great potential in the field of solar energy conversion due to their well‐studied photoredox activity (similar to TiO2 ) and good optical responsiveness of linkers, which serve as the antenna to absorb visible‐light. Although much effort has been dedicated to developing Ti‐MOFs with high photocatalytic activity, their solar energy conversion performances are still poor. Herein, we have implemented a covalent‐integration strategy to construct a series of multivariate Ti‐MOF/COF hybrid materials PdTCPP⊂PCN‐415(NH2 )/TpPa (composites 1, 2, and 3), featuring excellent visible‐light utilization, a suitable band gap, and high surface area for photocatalytic H2 production. Notably, the resulting composites demonstrated remarkably enhanced visible‐light‐driven photocatalytic H2 evolution performance, especially for the composite 2 with a maximum H2 evolution rate of 13.98 mmol g −1  h −1 (turnover frequency (TOF)=227 h −1 ), which is much higher than that of PdTCPP⊂PCN‐415(NH2 ) (0.21 mmol g −1  h −1 ) and TpPa (6.51 mmol g −1  h −1 ). Our work thereby suggests a new approach to highly efficient photocatalysts for H2 evolution and beyond. Abstract : A series of covalently connected multivariate Ti‐MOF/COF hybrid materials were constructed demonstrating outstanding photocatalytic H2 evolution performance with a maximum H2 evolution rate of 13.98 mmol g −1  h −1 (TOF=227 h −1 ), much higher than the prototypical counterparts.